Characterisation Of Fungi Associated With Diseased Cocoa (Theobroma Cacao) In West Coast Of Peninsular Malaysia - Rahim, Huda Shakirah Abd (2023)
Cocoa (Theobroma cacao) is an evergreen tree belonging to the Malvaceae family. The cacao plant has contributed significantly to the country's economy and has also become a source of income for smallholder farmers. However, fungal diseases are one of the major problems in cocoa plantations, where the spread of uncontrollable infections can lead to significant yield losses. The objective of this study was to identify and characterise the fungal isolates associated with diseased T. cacao in Malaysia through morphological, molecular, and pathogenicity analyses. Diseased samples of leaves, stems, and pods of T. cacao were collected from different plantations in Malaysia. Morphological and molecular analyses were carried out to identify the fungal isolates. Phylogenetic analysis was carried out to accurately identify and characterise the fungal isolates using various genes such as internal transcribed spacer (ITS), translational elongation factor 1-alpha (tef1-α), β-tubulin (tub2), glyceraldehyde-3-phosphate dehydrogenase (gapdh), and RNA polymerase subunit II (rpb2). To assess the pathogenic capabilities of the fungal isolates, pathogenicity tests were carried out on healthy leaves, stems, and pods of T. cacao using mycelial plugs with wound treatment. A total of 116 fungal isolates were isolated from diseased leaves, stems, and pods of T.